2000
DOI: 10.1007/pl00007938
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of half-mask respirator protection in styrene-exposed workers

Abstract: The protection afforded by negative-pressure half-mask respirators varies widely, which stresses the need to assess the effective reduction of exposure whenever these devices are introduced for St-exposed workers. If respirators are to be re-used for several days, their performance must be evaluated during the last shift of use. Measurement of urinary excretion of unmodified St proved a useful tool for the evaluation of respirator effectiveness in exposed workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…If the ethical problem can be resolved we will be able to ask the workers not to wear the respirator and to perform a comparison. In addition, it was reported that there was an increase in urinary MA during the working week 24,29,30) . This means that the excretion of MA in urine is influenced by the previous day's exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the ethical problem can be resolved we will be able to ask the workers not to wear the respirator and to perform a comparison. In addition, it was reported that there was an increase in urinary MA during the working week 24,29,30) . This means that the excretion of MA in urine is influenced by the previous day's exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Gobba et al reported 30%-90% by evaluating the decrease in urinary styrene excretion 24) . Inaoka et al mentioned 49% in winter and 45% in summer by calculating from the regression line between individual exposures and the urinary MA 25) .…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Gobba et al 7) seven workers were examined who processed styrene containing materials by means of rollers, brushes and spray guns. The authors determined the concentrations of metabolites in urine and compared the activities during one week with and without using a half face mask.…”
Section: Discussionmentioning
confidence: 99%
“…imize the health effects caused by styrene exposure the use of respiratory masks is required. This issue has been addressed already by several studies resulting in different conclusions due to the variation in methods with which the studies were performed [7][8][9][10] .…”
mentioning
confidence: 99%
“…(1) analytical recovery, (2) sampling rate and capacity, (3) reverse diffusion, (4) temperature effects, (5) factor effects, (6) storage stability, and (7) precision and accuracy (105 standard (EN 482) has different criteria depending on the usage of the sampler, but for compliance purposes the corresponding figure is 30% (106).…”
Section: Comparison Of the Performance Of Passive Samplers With Othermentioning
confidence: 99%